2016
DOI: 10.1007/s00384-016-2628-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported wellbeing and body image after abdominoperineal excision for rectal cancer

Abstract: PurposePatients with low rectal cancer are often operated with an abdominoperineal excision (APE) rendering them a permanent stoma. The surgical procedure itself, the cancer diagnosis, and the permanent stoma might all affect quality of life. The aim of this study was to explore wellbeing and body image 3 years after APE in a population-based cohort of patients.MethodsAll patients with rectal cancer operated with an APE between 2007 and 2009 were identified using the Swedish ColoRectal Cancer Registry. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
0
23
1
Order By: Relevance
“…Likewise, it is known that there is a greater difficulty for women to participate mainly because of their embarrassment in the questioning of their sex life, even when the questionnaires are applied individually without the presence of the researcher (3) . Despite this possible constraint on women in research participation, the female sex was predominant (18:11) in the present study, which is in agreement with other national studies (19,20) , but contrary to what happens in most international studies (16,23) . The mean age of our patients was 50.8 years.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Likewise, it is known that there is a greater difficulty for women to participate mainly because of their embarrassment in the questioning of their sex life, even when the questionnaires are applied individually without the presence of the researcher (3) . Despite this possible constraint on women in research participation, the female sex was predominant (18:11) in the present study, which is in agreement with other national studies (19,20) , but contrary to what happens in most international studies (16,23) . The mean age of our patients was 50.8 years.…”
Section: Discussioncontrasting
confidence: 39%
“…This helps us in understanding the subjectivity of the subject who experiences such changes and that QoL is about the influence of culture, values and personal satisfaction (1,22) , and also on the issue of the person's difficulties in expressing their perceptions through a structured questionnaire. The verbalization with their own words possibly translates the experience better and points to suggestions for both quantitative and qualitative studies (23) . In the present study, it was possible to observe that patients experienced changes that limited habitual living during the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings show that 80.1%, 36.2%, 30.1%, and 58.5% of Chinese CRC patients, respectively had body image problems, anxiety, depression, and distress in the early postoperative period. The prevalence of these problems at this stage was higher than reported for other stages in some previous studies . Psychological distress among cancer inpatients has been well identified and managed by the CLPS, but these severe body image problems have not attracted enough attention .…”
Section: Discussionmentioning
confidence: 54%
“…Stoma patients have significantly poorer body image, higher levels of depression, and worse QOL than non‐stoma patients, even after 4 or 5 years postoperation. In one study, a subset of rectal cancer patients (18%) with a permanent stoma described bodily limitations and psychological distress even 3 years after surgery . However, another study showed no differences in QOL, anxiety, and depression between individuals with a permanent stoma and those without a stoma after 8 years postoperation …”
Section: Introductionmentioning
confidence: 99%
“…Sexual dysfunction after rectal cancer treatment is a multifactorial problem with a broad spectrum of associated risk factors . Psychological factors such as libido, arousal, body image and self‐esteem may be important . The presence of a stoma seems to affect sexual life for many patients, and improved counselling both before and after surgery by stoma care therapists as well as other healthcare personnel may help these patients.…”
Section: Discussionmentioning
confidence: 99%